Răspuns :
(-2)^(3x+1) = - 2
3x + 1 = 1
3x = 1 - 1
3x = 0
x = 0
(-2)^(2x + 3) = - 32
(-2)^(2x + 3) = (-2)^5
2x + 3 = 5
2x = 5 - 3
2x = 2
x = 2 : 2
x = 1
3^(-2x + 5) = 27
3^(-2x + 5) = 3^3
-2x + 5 = 3
-2x = 3 - 5
-2x = -2
x = -2 : (-2)
x = 1
3x + 1 = 1
3x = 1 - 1
3x = 0
x = 0
(-2)^(2x + 3) = - 32
(-2)^(2x + 3) = (-2)^5
2x + 3 = 5
2x = 5 - 3
2x = 2
x = 2 : 2
x = 1
3^(-2x + 5) = 27
3^(-2x + 5) = 3^3
-2x + 5 = 3
-2x = 3 - 5
-2x = -2
x = -2 : (-2)
x = 1
a) (-2)^(3x+1) = - 2
[tex](-2)^{3x+1}=(-2)[/tex]
simplificam cu -2
3x + 1 = 1 ⇒3x = 1 - 1 ⇒ 3x = 0 ⇒
x = 0 ∈Z
b)(-2)^(2x + 3) = - 32
[tex] (-2)^{2x+3}=-32 \\ \\(-2)^{2x+3}=(-2)^{5} [/tex]...
simplificam cu -2
2x + 3 = 5 ⇒2x = 5 - 3 ⇒ 2x = 2 ⇒x = 2 : 2
x = 1 ∈Z
c)
[tex] (3)^{-2x+5}=27 \\ \\(3)^{-2x+5}=(3)^{3} [/tex]
simplificam cu 3
-2x + 5 = 3 ⇒-2x = 3 - 5 ⇒ - 2x = - 2
x = 1 ∈Z
[tex](-2)^{3x+1}=(-2)[/tex]
simplificam cu -2
3x + 1 = 1 ⇒3x = 1 - 1 ⇒ 3x = 0 ⇒
x = 0 ∈Z
b)(-2)^(2x + 3) = - 32
[tex] (-2)^{2x+3}=-32 \\ \\(-2)^{2x+3}=(-2)^{5} [/tex]...
simplificam cu -2
2x + 3 = 5 ⇒2x = 5 - 3 ⇒ 2x = 2 ⇒x = 2 : 2
x = 1 ∈Z
c)
[tex] (3)^{-2x+5}=27 \\ \\(3)^{-2x+5}=(3)^{3} [/tex]
simplificam cu 3
-2x + 5 = 3 ⇒-2x = 3 - 5 ⇒ - 2x = - 2
x = 1 ∈Z